The History of In Vivo Tuberculin Testing in Bovines: Tuberculosis, a “One Health” Issue - Good, Margaret; Bakker, Douwe; Duignan, Anthony; Collins, Daniel M. (Frontiers in Veterinary Science, 2018)
Tuberculosis (TB) is more than 3 million years old thriving in multiple species. Ancestral Mycobacterium tuberculosis gave rise to multiple strains including Mycobacterium bovis (M. bovis) now distributed worldwide with zoonotic transmission happening in both directions between animals and humans. M. bovis in milk caused problems with a significant number of deaths in children under 5 years of age due largely to extra-pulmonary TB. This risk was effectively mitigated with widespread milk pasteurization during the 20thC and fewer young children were lost to TB. Koch developed tuberculin in 1890 and recognising the possibility of using tuberculin to detect infected animals the first tests were quickly developed. Bovine TB (bTB) control/eradication programmes followed in the late 19thC/early 20thC. Many scientists collaborated and contributed to the development of tuberculin tests, to refining and optimising the production and standardisation of tuberculin and to determining test sensitivity and specificity using various methodologies and injection sites. The WHO, OIE and EU have set legal standards for tuberculin production, potency assay performance and intradermal tests for bovines. Now, those using tuberculin tests for bTB control/eradication programmes rarely, see TB as a disease. Notwithstanding the launch of the first-ever roadmap to combat zoonotic TB, many wonder if bTB is actually a problem?; is there a better way of dealing with bTB; might alternative skin test sites make the test ‘better’ and easier to perform; are all tuberculins used for testing equally good?; why haven’t alternative ‘better’ tests been developed? This review was prompted by these types of questions. This paper attempts to succinctly summarise the data from the literature from the late 19thC to date to show why TB, and zoonotic TB specifically, was and still is important as a ‘One Health’ concern, and that the necessity to reduce the burden of zoonotic TB, to save lives and secure livelihoods is far too important to await the possible future development of novel diagnostic assays for livestock before renewing efforts to eliminate it. Consequently, it is highly probable that the tuberculin skin test will remain the screening test of choice for farmed livestock for the considerable future.